Copper treatment activates mitogen-activated protein kinase signalling in rice - Yeh, Chuan-Ming; Hung, Wan-Chi; Huang, Hao-Jen (Physiologia plantarum, 2003)
It is well known that mitogen‐activated protein kinase (MAPK) pathways are modules involved in the transduction of extracellular signals to intracellular targets in all eukaryotes. In plants, it has been shown that MAPKs play a role in the signalling of biotic and abiotic stresses. To characterize signalling pathways involved in heavy metal‐induced stress responses, we examine whether plant MAPKs are also involved in this process. The analyses of mRNA levels of OsMAPK genes have shown that only OsMAPK2 mRNA transcripts increased within 12 h upon CuCl2 treatment in suspension cells and roots. An in‐gel kinase assay revealed that three protein kinases, approximate 42, 50, and 64‐kDa, were activated by CuCl2 treatments. The approximate 42‐kDa protein kinase displayed MAPK properties. Antioxidant, GSH, prevented copper‐induced kinase activity. Furthermore, we found that rice roots underwent a rapid cell death upon this copper treatment. The copper‐induced cell death of rice roots was partially blocked by MAPK kinase inhibitor, PD98059. These results suggest that the MAPK cascades may function in the plant heavy metal induced‐signalling pathway.